2020
DOI: 10.1093/ehjci/ehaa946.2113
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of suspected cardiac amyloidosis in aortic stenosis patients referred for transcatheter aortic valve implantation

Abstract: Background The prevalence of cardiac amyloidosis (CA) and aortic stenosis (AS) both increase with age. Transcatheter aortic valve implantation (TAVI) expands the number of patients (P) eligible for treatment of AS, emphasizing the need to understand the prevalence of CA in AS and its prognostic associations. Echocardiography with speckle tracking has emerged as a useful method to enhance the clinical suspicion and to provide prognostic information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The negative impact of CA on patients with AS was also confirmed when data were adjusted for publication bias. We confirmed that CA is associated to a worse prognosis in patients with AS even after a sensitivity analysis without the study including patients with only a probability of CA, based on echocardiographic strain analysis (19). Interestingly, the negative effect of CA on AS outcome appears to be reduced in older subjects, thus suggesting the importance of CA assessment especially in patients with AS younger than 80 years old.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The negative impact of CA on patients with AS was also confirmed when data were adjusted for publication bias. We confirmed that CA is associated to a worse prognosis in patients with AS even after a sensitivity analysis without the study including patients with only a probability of CA, based on echocardiographic strain analysis (19). Interestingly, the negative effect of CA on AS outcome appears to be reduced in older subjects, thus suggesting the importance of CA assessment especially in patients with AS younger than 80 years old.…”
Section: Discussionsupporting
confidence: 72%
“…The revision of full-length articles allowed the exclusion of fourteen studies due to wrong study design or irrelevant information in their content. Thus, seventeen studies ( 6 , 7 , 13 17 , 19 , 20 , 24 31 ), enrolling 1,988 subjects (1,658 AS alone and 330 AS with CA), were included in the qualitative and quantitative analyses of main patients with AS characteristics with and without CA (14 studies), difference in mortality (9 studies), and treatment strategy (10 studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations